Influenza Vaccination Coverage in Patients with Chronic Diseases: A Descriptive Analysis (Epidemiology, Biostatistics, and Public Health, 2025)
Background: Influenza is a major cause of morbidity and mortality worldwide. Individuals with chronic diseases are at greater risk of severe disease or complications. Annual influenza vaccination is fundamental to reduce the burden of disease. Patients with chronic diseases often remain hard to reach and vaccination coverage data are poorly available. The aim of this study is to evaluate the influenza vaccination coverage in subjects from 6 months to 64 years of age with chronic diseases during the 2023/2024 season in Siracusa Local Health Authority, Italy.Methods: Records of influenza vaccination during 2023/2024 vaccination campaign were matched with the information on chronic diseases. The dataset included information on sex, age, influenza vaccine, chronic diseases, other vaccines administered. Results: During 2023/24 influenza season, vaccination coverage among the study population was 16.3% and it significantly differed, depending on the underlying disease. The higher VCs were reached in patients with chronic lung diseases (2627/5596; 46.9%), cardiovascular diseases (3250/7009; 46.4%) and chronic liver diseases (105/250; 42.0%), while the lower values were reached in patients with cancers (652/5630; 11.6%) and in patients with chronic inflammatory diseases and bowel malabsorption syndromes (159/1260; 12.6%).Conclusions: Although influenza vaccination is a safe, effective, and cost-effective method of preventing influenza infection and its complications, VC rates are not satisfactory, and coverage target indicated by Health Authorities remained very far. Reversing this is likely to require a broad range of interventions on patients, caregivers, parents, healthcare providers and health communication.
Keywords: influenza; influenza vaccination; Vaccination coverage; prevention; chronic diseases; high risk patients; health communication